STRATEGI ADAPTASI PEDAGANG PENSI DAN LANGKITANG DI PEKANBARU - Debby Febrianti; Achmad Hidir (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This study examines the adaptation strategies of pensi and langkitang traders in Pekanbaru, Pensi and langkitang are clams that live in fresh water and one of the traditional culinary preparations typical of West Sumatra. In Pekanbaru, there are also many street vendors selling pensi and langkitang, even special seafood restaurants have also mushroomed. The objectives of this study are to find out: 1) The adaptation strategy of pensi and langkitang traders in Pekanbaru 2) Obstacles experienced by pensi and langkitang traders in Pekanbaru. This research uses qualitative research methods. The theory used by Pierre Bourdieu's theory of Adaptation Strategies. The informants in this study were 5 people who were pensi and langkitang traders. The results of this study are 1)Biological investment strategies by sending their children to college in order to get a better job 2)Successful strategies by making savings, increase selling time and promote selling goods on social media 3) Educational strategies by finding information about how to process pensi and langkitang from friends and relatives 4) Economic investment strategies by lending to relatives and cooperatives, having a side job, establishing relationships with certain parties that are beneficial to him. The obstacles faced are due to the small business so that income is uncertain, lack of knowledge about online marketing or using social media.